2013
DOI: 10.1371/journal.pone.0058328
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behaviour and Physical Activity in South Asian Women: Time to Review Current Recommendations?

Abstract: ObjectiveOur aims were to describe activity and sedentary behaviours in urban Asian women, with dysglycaemia (diagnosed at recruitment), and without dysglycaemia and examine the relative contribution of these parameters to their glycaemic status.Methods2800 urban women (30–45 years) were selected by random cluster sampling and screened for dysglycaemia for a final sample of 272 newly diagnosed, drug naive dysglycaemic and 345 normoglycaemic women. Physical activity and sedentary behaviours were assessed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…In the present study, lower baseline PA during transport was consistent with those of other studies (29)(30)(31). It is recommended that programing to promote and support walking and cycling as daily trips can significantly provide the situation for regular PA (32).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, lower baseline PA during transport was consistent with those of other studies (29)(30)(31). It is recommended that programing to promote and support walking and cycling as daily trips can significantly provide the situation for regular PA (32).…”
Section: Discussionsupporting
confidence: 92%
“…Physical activity or inactivity did not contribute to pattern 2. However, in a previous analysis of physical activity in this population ( 16 ) , the mean physical activity has been found to be higher than the recommended energy expenditure on physical activity for health benefits based on global guidelines across the population, which may possibly explain why physical activity did not emerge as a component of pattern 2 or 1.…”
Section: Discussionmentioning
confidence: 68%
“…The only study in this direction has been that of clustering of energy-related behaviour in children through PCA ( 15 ) . Our previous analysis of physical activity in urban women has shown that dysglycaemia is prevalent despite high levels of physical activity and low sedentary behaviour, necessitating further study of lifestyle in its entirety ( 16 ) . PCA has traditionally been used for analysing variables obtained through frequency questionnaires, but conceptually quantification such as the use of food portion sizes and metabolic equivalents for physical activity would allow a better representation of actual real-life patterns.…”
mentioning
confidence: 99%
“…The concept of ethnicity specific recommendation for physical activity has been discussed elsewhere. A recent study in Sri Lankan women demonstrated women who self-reported less than 2,640 MET-minutes.week -1 of moderate to vigorous physical activity (~400–800 minutes per week of moderate intensity physical activity) are more likely to exhibit impaired glycaemia compared to women with self-reported weekly activity greater than this threshold (sensitivity 84% and specificity 85%) [ 36 ]. Although that study supports the concept of greater physical activity requirements for South Asian women, it is important to recognize that the use of self-reported questionnaires substantially overestimates physical activity [ 37 ] and limits the analysis exploring the actual dose-response relationship between physical activity and glycaemia.…”
Section: Discussionmentioning
confidence: 99%